Emotional outcomes after stroke: factors associated with poor outcome. - Dennis, M; O'Rourke, S; Lewis, S; Sharpe, M; Warlow, C (2000)
OBJECTIVES: The impact of stroke on the emotional outcome of patients is large. The aim was to describe the emotional outcomes among a cohort of patients which was of sufficient size to provide a precise estimate of their frequency and help identify those factors which are associated with poor outcomes after an acute stroke. METHODS: 372 surviving patients, who had been referred to a hospital and entered into a randomised trial to evaluate a stroke family care worker, were asked to complete questionnaires at a 6 month follow up. These included measures of emotional distress (general health questionnaire 30 item, hospital anxiety and depression scale) and physical functioning (modified Rankin, Barthel index). A regression analysis was used to identify factors which were independently associated with poor outcomes. RESULTS: 184 (60%) surviving patients scored more than 4 on the GHQ-30, 55 (22%) more than 8 on the HAD anxiety subscale, and 49 (20%) more than 8 on the HAD depression subscale. Patients with severe strokes resulting in physical disability were more likely to be depressed whereas there was a less strong relation between disability and anxiety. Patients with posterior circulation strokes had consistently better emotional outcomes than those with anterior circulation strokes. CONCLUSIONS: These data may help identify those patients at greatest risk of poor emotional outcomes and thus help in planning trials and delivering appropriate interventions.